Las puzolanas y el ahorro energético en los materiales de construcción - Soria Santamaría, Francisco (Materiales de Construcción, 1983)
This discussion commences with some general comments on the energy crisis and its impact on the cement industry, with the corresponding coal reconversion problems. Three factors are highlighted where saving has been centered: technological process, raw materials and finished product, emphasizing the interest of latter which includes incorporating active additions in Portland cement.A quick review then follows about pozzolanas, their origin, definitions and classification. Their chemical composition is underlined, and the concept of pozzolanic activity is described.Later on, pozzolanic cements, their most significant properties and the advantages of using pozzolana are explained.After a lengthy description about possible applications of pozzolanas and pozzolanic cements, the conclusion reviews current trends in international standards for such cements and possible evolution in consumption of additions by the year 2000, with a view to saving more energy, without impairing the essential properties of the cement.